Identification of Phenolic Compounds and Antimicrobial Activity of Roots of Arbutus unedo L. - Dib, M.A.; Djabou, N.; Allali, H.; Tabti, B. (Asian Journal of Chemistry, 2010)
The roots of Arbutus unedo L. were extracted with a water/methanol/acetone mixture. Two major compounds, (+)-catechin and (+) catechin gallate were identified by NMR spectroscopy. A number of phenolic compounds were also identified by gas chromatography couples to mass spectrometry (GC-MS) as benzeneacetic acid 4 hydroxy, caffeic acid, gallic acid, protocatechic acid and bis(2-ethylhexyl) phthalate. Analysis of the non-volatile and thermolabile phenolic compounds by GC-MS presupposes their conversion into volatile and thermotolerant derivatives. Preliminary investigations on microbiological activity showed that examined aqueous and alcoholic extracts from Arbutus unedo L. root have weak activity against gram-negative and gram-positive organisms as well as a weak antifungal activity.